Optimal PV and Battery Sizing for a Space Microgrid Near the Lunar South Pole Considering ISRU, Habitat and Water Subsystem Power Demand - Saha, Diptish; Bazmohammadi, Najmeh; Vasquez, Juan C.; Guerrero, Josep M. (2023 International Conference on Environmental Systems, 2023)
Diptish Saha, Aalborg University, Denmark Najmeh Bazmohammadi, Aalborg University, Denmark Juan C. Vasquez, Aalborg University, Denmark Josep M. Guerrero, Aalborg University, Denmark ICES501: Life Support Systems Engineering and Analysis The 52nd International Conference on Environmental Systems was held in Calgary, Canada, on 16 July 2023 through 20 July 2023. The size and mass of the payload substantially affect the cost of space missions. The aim of this paper is to investigate the optimal mass and size of the photovoltaic (PV) array and battery in a PV-battery-powered lunar microgrid (MG) at 15 highly illuminated candidate sites near the lunar south pole. It is assumed that PV arrays are installed on top of towers with a height of 10 m. The methodology to estimate the PV output power at each candidate site using the illumination time-series profile is presented. On the consumption side, the power demand profiles of ISRU and wastewater subsystems are determined using the estimated oxygen and water consumption profiles of the habitat with four crew members. The closed-loop model of water management includes the interaction of ISRU, wastewater filtration system, and the crew habitat. The power consumption profile of the crew habitat is generated considering different power-consuming components in the habitat as well as the daily schedule of the crew members. Organizing different loads in a multi-microgrid system is also investigated. Finally, a criterion, mass-per-unit-load (MPUL), is used to compare different sites and select the best location with the minimum PV-battery system mass that can serve the highest power demand.